Top ten investments to beat the crunch! : invest your way to success in a downturn - Mellon, Jim (J. Wiley & Sons, 2009)
"Bestselling authors Jim Mellon and Al Chalabi were seen as the party poopers just a few years ago when they predicted the financial crisis in Wake Up! Now they take the opposite view - the party is about to start. It won't last forever, but in a few years a lot of money can be made by the astute and well-informed. This is your step-by-step introduction to the world of investment - including all the Big ideas seasoned investors are searching for"--Resource description page.